2009
DOI: 10.3171/2009.2.jns081622
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcome of seizures after spontaneous intracerebral hemorrhage

Abstract: Object. Seizures are an important neurological complication of spontaneous intracerebral hemorrhage (ICH).A better understanding of the risk factors of seizures following ICH is needed to predict which patients will require treatment.Methods. Two hundred and forty-three adult patients were enrolled in this 1-year retrospective study. Multiple logistic regression was used to evaluate the relationship between baseline clinical factors and the presence or absence of seizure during the study period.Results. Seizur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 22 publications
2
42
3
Order By: Relevance
“…We found in this study that the occurrence of ESs seems to be correlated with cortical hemispheric hemorrhage localization. This finding is similar to the findings of other previous investigations [4,7,25] . The lobar localization of a hemorrhage has been described as a predictor of ESs following ischemic stroke and sICH owing to potential cortical involvement in comparison to deep sICH [9,26,35] .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found in this study that the occurrence of ESs seems to be correlated with cortical hemispheric hemorrhage localization. This finding is similar to the findings of other previous investigations [4,7,25] . The lobar localization of a hemorrhage has been described as a predictor of ESs following ischemic stroke and sICH owing to potential cortical involvement in comparison to deep sICH [9,26,35] .…”
Section: Discussionsupporting
confidence: 83%
“…It is difficult to compare the incidence rates of ESs reported in the literature owing to differences in the methods used, including variables like inclusion criteria, previous seizures, or time window in defining ESs. For example, several studies with a short follow-up period of 7 days reported incidence rates of ESs in patients following sICH that ranged between 1 and 12% [25][26][27] . Other studies with short follow-up periods of 24 h up to 14 days revealed incidence rates of ESs following sICH of 4-8% [6-8, 15, 28] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently presented data on patient populations similar to ours also demonstrated an association of younger age with seizures. 3,23,24 This association might reflect the higher survival of younger ICH patients. Differences in the clinical manifestation of epilepsy in elderly and younger adults can lead to underestimation of epilepsy incidence in older people.…”
Section: Discussionmentioning
confidence: 99%
“…1,[21][22][23] Despite the different design of these studies (mixed population of hemorrhagic and ischemic stroke), age below 65 years was revealed as a factor associated with seizures after ICH. Recently presented data on patient populations similar to ours also demonstrated an association of younger age with seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation